2019
DOI: 10.1111/jsr.12860
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sleep deprivation on objective and subjective measures of facial appearance

Abstract: The faces of people who are sleep deprived are perceived by others as looking paler, less healthy and less attractive compared to when well rested. However, there is little research using objective measures to investigate sleep‐loss‐related changes in facial appearance. We aimed to assess the effects of sleep deprivation on skin colour, eye openness, mouth curvature and periorbital darkness using objective measures, as well as to replicate previous findings for subjective ratings. We also investigated the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…When in the lab, participants completed the KWA ina private room. During the test day, participants completed multiple other tests (all between 10:00 h and 17:30 h), the results of some of which have been published previously (e.g., Holding et al, 2017Holding et al, , 2019a. Lunch for all participants was provided at 12:00 h and a lighter snack was available at 15:45 h.…”
Section: Methodsmentioning
confidence: 99%
“…When in the lab, participants completed the KWA ina private room. During the test day, participants completed multiple other tests (all between 10:00 h and 17:30 h), the results of some of which have been published previously (e.g., Holding et al, 2017Holding et al, , 2019a. Lunch for all participants was provided at 12:00 h and a lighter snack was available at 15:45 h.…”
Section: Methodsmentioning
confidence: 99%
“…In the late bedtime group, the physiological indicators of skin barrier property, including skin hydration content, TEWL and sebum content, were significantly altered, which was also observed in many other researches on the relationship between sleep conditions, such as poor sleep, short-term or long-term sleep deprivation, and skin physiological characteristics. 11–13 , 27 , 28 We argued that the underlying mechanism that caused this impairment of the skin barrier was likely to be associated with circadian rhythms, which have been demonstrated previously to regulate and affect skin function. 29 , 30 It was reported that epidermal and hair follicle keratinocytes, dermal fibroblasts and melanocytes present circadian oscillators, which affect cell migration and proliferation, wound healing and susceptibility of the tissues to damage.…”
Section: Discussionmentioning
confidence: 84%
“…Obviously, late bedtime has developed into a new sleep habit. To date, current evidence has been focusing on the effects of insufficient sleep or sleep deprivation on skin characteristics, 11 , 13 , 27 , 28 yet little is known about whether bedtime has any impact on the skin status, particularly on the skin microbiome. Thus, to the best of our knowledge, the current study is the first attempt to investigate the effects of regular late bedtime on facial skin and skin bacterial microbiota in healthy women.…”
Section: Discussionmentioning
confidence: 99%
“…The second major impact of sleep falls on their work productivity (24.23%) followed by health (22.59%). Various clinical surveys also have shown in the past that insufficient sleep does impact health and appearance adversely [31,32]. A relatively lower percentage of students considered that sleep affects their academic performance (14.08%) or their ability to socially interact with others (13.20%).…”
Section: Fig 16: Graph Showing Distribution Of Various Effects Of Insufficient Sleep On Undergraduate Studentsmentioning
confidence: 99%